CONECT study: A prospective observational study on comparative nutritional efficacy in critically ill patients receiving ready-to-use vs. compounded parenteral nutrition - Diogo Oliveira Toledo; Gabriel Bernardes Yacoub; Enzzo de Almeida Gallafassi; Fernanda Antunes Ribeiro; Julieta Regina Moraes; Priscila Barsanti de Paula Nogueira; Daniel Tavares Malheiro; João Manoel Silva, Jr. (Clinical Nutrition Open Science, 2025)
Summary: Introduction: Critically ill patients often require parenteral nutrition (PN), however the clinical and economic impact of ready-to-use diets compared to compounded diets is not well understood. This study aimed to analyze the safety and cost-effectiveness of these nutritional strategies. Methodology: A prospective observational study was conducted with patients requiring parenteral nutritional therapy. Data on nutritional composition, costs, and complications were collected, and propensity score adjustment was applied to the total sample to ensure an appropriate balance between the ready-to-use diet and the compounded diet groups. Cost calculations were adjusted for diet duration. Outcomes included total complications, mortality, cost per avoided complication, and cost per life saved. Results: A total of 398 patients were screened, and 329 were included. Following propensity score adjustment, the study included 50 patients, with 25 in each group. The compounded diet showed a higher supply of proteins and lipids, resulting in significantly higher levels of triglycerides (451.11 mg/dL vs. 120.22 mg/dL), pre-albumin (27.24 mg/dL vs. 14.24 mg/dL), glucose (144.32 mg/dL vs. 123.93 mg/dL), and urea (75.6 mg/dL vs. 56.3 mg/dL) in the first week, with persistently elevated levels over four weeks. Although the compounded diet exhibited a lower daily complication rate (0.96 vs. 2.14), the daily mortality rate was higher (0.32 deaths/day vs. 0.14 deaths/day), with no statistically significant difference (P = 0.34). The total cost during the administration of the diet was USD 129,919.00 for the ready-to-use diet and USD 331,525.00 for the compounded diet, resulting in a total incremental cost of USD 201,606.00 over 25 days. The cost per avoided complication was USD 11,121.07 for the ready-to-use diet and USD 12,730.54 for the compounded diet, while the cost per life saved was USD 727.55 for the ready-to-use diet and USD 4,243.51 for the compounded diet. Conclusion: Compounded PN resulted in higher costs without a statistically significant difference in complications or mortality when compared to the ready-to-use diet. These findings highlight the need for further studies to evaluate the clinical and economic impact of different parenteral nutrition strategies before large-scale implementation.